2017
DOI: 10.1093/humrep/dex339
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing of gay fathers with children born through surrogacy: a comparison with lesbian-mother families and heterosexual IVF parent families

Abstract: This research was supported, under the auspices of the Open Research Area (Application BO 3973/1-1; Principal Investigator, Michael E Lamb), by grants from the UK Economic and Social Research Council (ESRC; Grant ES/K006150/1; Principal Investigator, Michael E. Lamb), The Netherlands Organisation for Scientific Research (NWO; Grant NWO 464-11-001, Principal Investigator, Henny W.M. Bos) and the French Agence Nationale de Recherche (ANR; Grant ANR-12-ORAR-00005-01, Principal Investigator, Olivier Vecho) whose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
1
31
2
3
Order By: Relevance
“…The lack of difference between gay fathers through surrogacy, gay fathers through a heterosexual relationship, and heterosexual fathers on reported symptoms of depression is in line with those of a previous study showing no differences between gay fathers through surrogacy and heterosexual fathers on parental stress, depression, and anxiety (Van Rijn-van Gelderen et al, 2018). Similarly, the absence of difference between the fatherhood groups on most Big Five personality dimensions has echoed findings from previous studies suggesting no profound differences in general between gay and heterosexual men on personality traits (e.g., Greaves et al, 2017;Ifrah et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of difference between gay fathers through surrogacy, gay fathers through a heterosexual relationship, and heterosexual fathers on reported symptoms of depression is in line with those of a previous study showing no differences between gay fathers through surrogacy and heterosexual fathers on parental stress, depression, and anxiety (Van Rijn-van Gelderen et al, 2018). Similarly, the absence of difference between the fatherhood groups on most Big Five personality dimensions has echoed findings from previous studies suggesting no profound differences in general between gay and heterosexual men on personality traits (e.g., Greaves et al, 2017;Ifrah et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…While comparisons between different pathways to gay fatherhood are scarce, some comparisons between gay fathers through surrogacy and heterosexual fathers via assisted reproduction have been conducted. Van Rijn-van Gelderen et al (2018) for example compared the well-being of gay fathers through surrogacy with heterosexual IVF parent families from three European countries (United Kingdom, the Netherlands, and France) and found no differences on parental stress, depression, anxiety, or relationship satisfaction between the two groups. Shenkman et al (2018), compared Israeli gay fathers with children from a previous heterosexual relationship and heterosexual fathers and found gay fathers reported higher levels of personal growth (feelings of continued development and self-improvement alongside a sense of personal fulfillment).…”
Section: Pathways To Gay Fatherhoodmentioning
confidence: 99%
“…Before parents came to our institutions for T2, they were again queried about the division of labor using a password-protected online questionnaire. During both visits, other data outside the scope of the current study were also collected (e.g., see Van Rijn -van Gelderen et al (2018) for further information). The retention rate at T2 for the current analytic sample was 90.9%.…”
Section: Methodsmentioning
confidence: 99%
“…While gay fathers reported high overall levels of relationship satisfaction, those who reported greater discrepancies between actual and ideal divisions of labour also reported decreased levels of relationship satisfaction, including fewer affectionate expressions and less interpersonal agreement with partners. A cross-sectional study by Van Rijn-van Gelderen et al (2018) found no differences in parental wellbeing among gay fathers with infants conceived through surrogacy, lesbian families with infants conceived through donor insemination, and heterosexual families with infants conceived through IVF. All three parent groups reported relatively low levels of parental stress, anxiety and depression and were relatively satisfied with their intimate relationships, even after controlling for whether they were primary or secondary caregivers.…”
Section: Discussionmentioning
confidence: 97%